2007
DOI: 10.1021/jp0732458
|View full text |Cite
|
Sign up to set email alerts
|

White-Light-Induced Fragmentation of Methane

Abstract: We experimentally probe molecular ionization and dissociation of methane molecules in the gas phase upon their irradiation by intense pulses of white light that spans the wavelength range 500-850 nm. White light pulses are generated upon irradiation of BK7 glass by 36-fs-long pulses of intense 820 nm laser light. Comparison is made of the molecular fragmentation patterns obtained using white light that is depolarized with those obtained using single-color (820 nm) light that is highly chirped. On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…2b). This supercontinuum was generated by irradiating 1 cm long BK-7 glass with intense 800 nm light; the methodology adopted for such white light experiments on molecules, including estimation of the white light intensity, has been described elsewhere recently [17]. The resulting TOF spectrum also shows dissociation occuring, with prominent fragments S + and CS + , whose yields relative to, say, CS 2+ 2 are consistent with those obtained in data obtained using single-color light pules of 40, 100 fs duration ( Fig.…”
mentioning
confidence: 99%
“…2b). This supercontinuum was generated by irradiating 1 cm long BK-7 glass with intense 800 nm light; the methodology adopted for such white light experiments on molecules, including estimation of the white light intensity, has been described elsewhere recently [17]. The resulting TOF spectrum also shows dissociation occuring, with prominent fragments S + and CS + , whose yields relative to, say, CS 2+ 2 are consistent with those obtained in data obtained using single-color light pules of 40, 100 fs duration ( Fig.…”
mentioning
confidence: 99%
“…The resulting local anisotropy degrades the uniformity of polarization. In the case of experiments in BK7 glass, we have imaged the filamentation along the transverse direction and have correlated the highly inhomogeneous regions of multiple filamentation with depolarization of the propagated beam [29]. In the case of gases like Ar, we observed that with increase in the gas pressure beyond 1.4 atm, there is a degradation of the extinction ratio [30] that is brought about by non-uniformities in the refractive index (or electron density) within the plasma.…”
Section: Resultsmentioning
confidence: 94%
“…Apart from our experiments, other evidence has been obtained of the breakdown of adiabatic, single-activeelectron dynamics in molecules in studies of the wavelength dependence of ionization and fragmentation of hydrocarbon molecules [19]; multielectron excitation results in formation of molecular ions in highly excited states. Unexpectedly high KERs accompany dissociation of such states [20], as is seen in Fig. 3.…”
mentioning
confidence: 75%